CORRELATION BETWEEN KNOWLEDGE WITH PARTICIPATION LEVEL AT POSYANDU ORCHID WITH CHILDREN UNDER FIVE NUTRIENT STATUS IN VILLAGE PED NUSA PENIDA SUB DISTRICT - Niluh ayu Padma Dewi (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2018)
Posyandu is one form of Community Resource Health Effort (UKBM) that is managed and organized from, by, for and with the community. One indicator of program coverage in Posyandu called D / S is the number of children under five who come to Posyandu in sharing with the number of children under five in the area, indicating the level of community participation in Posyandu activities. The aim of research is Correlation Between Knowledge With Participation Level At Posyandu Orchid With Children Under Five Nutrient Status in Village Ped Nusa Penida sub district.This research is an observational research with cross sectional design. The sample research is mother of toddler who have children aged 12 - 59 months. Relationship test analysis used is Rank Sperman Test. The result research is knowledge level with the participation of mother of toddler is enough knowledge with good participation of 53 mother (31,1%) with ? = 0,036. So it can be concluded is a relationship between the level of knowledge and participation. Whereas for the level of participation rate both with good nutritional status is 88 toddlers (51.8%) with a value of ? = 0.034. So it can be concluded is a relationship between participation with nutritional status of children.Keywords: Knowledge, Participation, Nutrient Status